2020
DOI: 10.1016/j.transci.2020.102897
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring haemophilia A prophylaxis with BAY 81-8973: A case series

Abstract: BAY 81-8973 is an unmodified, full-length third generation recombinant factor VIII (rFVIII) which offers a more favorable pharmacokinetic (PK) profile, compared to its predecessor sucrose-formulated rFVIII (rFVIII-FS). We here report on a retrospective case series of nine patients affected by hemophilia A (HA), with variable disease severity, bleeding phenotype and comorbidities, to underline our clinical practice on prophylaxis with a recently introduced standard hall-life recombinant Factor VIII. The current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Megias's study showed that PK‐guided prophylaxis facilitated an adequate level of bleeding control in patients with haemophilia A and maintained clinical variables and patient convenience in an integrative manner without more FVIII consumption 18 . In a previous report of case series, PK‐guided prophylaxis showed the ability to attain improved joint function and an increase in quality of life 20 . Another study of Nuwiq showed an overall dose reduction of 7.2% in PK‐guided personalized prophylaxis (compared with standard prophylaxis), which not only provided good bleeding protection but also increased dosing interval to twice or less in many patients 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Megias's study showed that PK‐guided prophylaxis facilitated an adequate level of bleeding control in patients with haemophilia A and maintained clinical variables and patient convenience in an integrative manner without more FVIII consumption 18 . In a previous report of case series, PK‐guided prophylaxis showed the ability to attain improved joint function and an increase in quality of life 20 . Another study of Nuwiq showed an overall dose reduction of 7.2% in PK‐guided personalized prophylaxis (compared with standard prophylaxis), which not only provided good bleeding protection but also increased dosing interval to twice or less in many patients 21 .…”
Section: Discussionmentioning
confidence: 99%
“…18 In a previous report of case series, PK-guided prophylaxis showed the ability to attain improved joint function and an increase in quality of life. 20 Another study of Nuwiq showed an overall dose reduction of 7.2% in PK-guided personalized prophylaxis (compared with standard prophylaxis), which not only provided good bleeding protection but also increased dosing interval to twice or less in many patients. 21 PK-guided prophylaxis can improve prophylaxis efficacy and reduce FVIII concentrate consumption in developed countries.…”
Section: Ta B L E 2 Pk Parameters and Dosing Regimensmentioning
confidence: 99%
“…Since the administration is often performed weekly and since the start is usually before or at 1 year of age, prophylaxis involves a significant burden for both, patients and families. While there is an aim to tailor the frequency of prophylactic FVIII/FIX infusions to the patient's needs and his lifestyle, still zero joint bleedings remain the ultimate goal, given the fact that even a single bleed may initiate joint damage 1,2 …”
mentioning
confidence: 99%
“…While there is an aim to tailor the frequency of prophylactic FVIII/FIX infusions to the patient's needs and his lifestyle, still zero joint bleedings remain the ultimate goal, given the fact that even a single bleed may initiate joint damage. 1,2 However, despite proper prophylactic treatment, joint bleeding with potential joint damage frequently occurs and thereof regular joint evaluation is an important part of hemophilia disease monitoring. Besides clinical examination, radiographs, ultrasound, and magnetic resonance imaging (MRI) might be used for noninvasive joint diagnosis.…”
mentioning
confidence: 99%